Isolation and Screening of Thermo stable Extracellular Alkaline Protease Producing Bacteria from Tannery Effluents - Habib, S. M. A.; Fakhruddin, A. N. M.; Begum, S.; Ahmed, M. M. (Journal of Scientific Research, 2012)
The aim of the current study was to isolate extracellular protease producing bacteria from tannery effluents. The isolation was performed by serial dilution and plating method. Eight protease producing isolates were screened out on the basis of their clear zone formation on skim milk agar as well as production of protease in protease producing broth. They were identified on the basis of cultural, morphological and biochemical tests. Among the eight isolates, 3 isolates were found to belong to the genus Halobacterium, and the rest 5 isolates were found to belong to genus Actinobacillus. Among the eight protease producing isolates, one of the isolates was selected as promising protease producer and designated as Halobacterium sp. AF1. Keywords: Actinobacillus; Detergent; Halobacterium; Protease; Proteolytic activity; Tannery. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.6976 J. Sci. Res. 4 (2), 515-522 (2012)